2020
DOI: 10.1177/1178632920977894
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ Views on the Implementation Potential of a Stratified Treatment Approach for Low Back Pain in Germany: A Qualitative Study

Abstract: Stratified care for low back pain (LBP) has been shown to be clinically- and cost-effective in the UK, but its transferability to the German healthcare system is unknown. This study explores LBP patients’ perspectives regarding future implementation of stratified care, through in-depth interviews (n = 12). The STarT-Back-Tool was completed by participants prior to interviews. Interview data were analysed using Grounded Theory. The overarching theme identified from the data was ‘treatment-success’, with subthem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 53 publications
1
8
0
Order By: Relevance
“…First, digital therapy apps provide a scalable and broadly accessible approach, enabling the treatment of LPB in rural areas and when the availability and workload of physiotherapists are limited [ 15 ]. Moreover, although stratified care is not yet implemented in routine care in Germany (eg, using the STarT-Back questionnaire), digital therapy apps enable early and immediate utilization for patients at high risk for developing a worsening or chronic condition [ 16 , 17 ]. Digital therapeutic care apps also support self-management and increase the patient’s literacy through in-depth educational information [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…First, digital therapy apps provide a scalable and broadly accessible approach, enabling the treatment of LPB in rural areas and when the availability and workload of physiotherapists are limited [ 15 ]. Moreover, although stratified care is not yet implemented in routine care in Germany (eg, using the STarT-Back questionnaire), digital therapy apps enable early and immediate utilization for patients at high risk for developing a worsening or chronic condition [ 16 , 17 ]. Digital therapeutic care apps also support self-management and increase the patient’s literacy through in-depth educational information [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Gcelu et al also reported that, “medical schools have to introduce students to the diagnosis and treatment of MSKD disorders early, general physicians and other specialists need to have greater exposure to these conditions and primary care workers should be trained to manage these MSKD disorders” [ 13 ]. The risky effects of manual work which is related to physical injury (be it microtrauma) has been well documented and is where the biomedical model of management stems [ 20 ]. However, due to the multifactorial nature of CLBP, this model (biomedical) alone failed to explain the mosaic of the pathophysiology of CLBP disability [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, due to the multifactorial nature of CLBP, this model (biomedical) alone failed to explain the mosaic of the pathophysiology of CLBP disability [ 55 ]. Thus, evidence has shown limited effectiveness of this traditional approach to management [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Qualitative research into the views of patients and clinicians on the use of risk-based strati ed care for LBP in Germany [30,31] found that patients were not convinced about the idea of being matched to treatments based on their risk of poor outcome and placed greater importance on receiving a diagnosis for their pain condition. Whilst GPs in the present study reported that patients presenting with MSK pain commonly had the expectation of being referred for imaging in order to identify the underlying cause of their pain, they were able to manage these expectations through using strati ed care to facilitate negotiation between the risk-matched treatment options and patients' preferences.…”
Section: Comparison With Previous Research Literaturementioning
confidence: 99%